P46 Case report: a patient with human immune deficiency virus mimicking systemic lupus erythematosus. (23rd March 2020) - Gokcen, Neslihan; Kaya, Hacer; Tuncer, Fatma; Yazici, Ayten; Cefle, Ayse
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by various clinical presentations. Human immune deficiency virus (HIV) causes acquired immune deficiency syndrome (AIDS) in case of progression of the infection. Patients with HIV can present different rheumatologic findings including arthralgia, arthritis, myalgia, myositis, vasculitis, and gout. We herein present a patient mimicking SLE who was diagnosed with HIV. Methods: A 40-year-old man presented with a 3-month history of oral lesions and a 2-month history of blurry vision, vertigo, speech difficulty, and ataxic gait. His past medical history was unremarkable. His vital findings were within normal ranges. There were two oral lesions that were greater than 10 mm in diameter localized on the hard palate and tongue. Cerebellar tests including gait, finger-to-nose, and heel-to-shin were abnormal. He could not walk in tandem gait. However, muscle strength and sensory exam were normal. On laboratory outcomes, fasting blood glucose, blood urea nitrogen, creatinine, and thyroid-function tests were normal. The rest of laboratory data were as follows: ALT 129 U/L, AST 102 U/L, GGT 72 U/L, hemoglobin 12.3 mg/L, WBC 3.6×10 3 /mcL, neutrophil count 1.8×10 3 /mcL, lymphocyte count 1.2×10 3 /mcL, CRP 1.5 mg/dl (normal, ≤5 mg/dl), ESR 42 mm/h. Cranial MRI was reported as multiple hyperintense spots located on supratentorial white matter, corpus callosum, and brainstem on standard T2-weighted MRI sequence. On neurological consultation, these lesions were interpreted as encephalitis. Additionally, he was consulted to Ophthalmologist due to blurry vision. No pathological finding was found. He was also for autoimmune disorders causing cerebral involvement. Thus, ANA, ENA, anti ds DNA, ANCA were investigated. All autoantibodies, hepatitis screening, CMV, EBV, parvovirus B 19 were found negative. On the other hand, HIV positivity was detected by ELISA. Consequently, the patient was transferred to department of Infectious diseases. Conclusion: HIV causes autoimmune and systemic disorders via triggering immune dysregulation. The frequency of these autoimmune diseases has ranged from 1% to 60% according to literature. Both HIV and the treatment of HIV can cause rheumatologic findings.